2010
DOI: 10.1002/mnfr.200900512
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and increased risk of cancer: Does decrease of serum 25‐hydroxyvitamin D level with increasing body mass index explain some of the association?

Abstract: Low levels of vitamin D and excess body weight are both factors associated with increased risk of cancer. The increased risk seems to be proportional to the increase in BMI, and to decrease in serum 25-hydroxyvitamin D (25(OH)D) level. Our earlier investigations suggest that serum 25(OH)D levels decrease with increasing BMI. Although the connection between cancer risk, BMI and vitamin D status might be arbitrary, it has not been discussed in the literature so far. In this study, we analyze data published in cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 50 publications
2
31
1
2
Order By: Relevance
“…One group would be women who are overweight or obese. The idea is consistent with literature information that obesity is usually correlated with low serum levels of 25-hydroxyvitamin D3, which was projected to be responsible for 20% of the cancer risk linked to increased body mass index (50). Another group would be postmenopausal women who receive hormone replacement therapy, which are known to increase their cancer risks.…”
Section: Discussionsupporting
confidence: 90%
“…One group would be women who are overweight or obese. The idea is consistent with literature information that obesity is usually correlated with low serum levels of 25-hydroxyvitamin D3, which was projected to be responsible for 20% of the cancer risk linked to increased body mass index (50). Another group would be postmenopausal women who receive hormone replacement therapy, which are known to increase their cancer risks.…”
Section: Discussionsupporting
confidence: 90%
“…As in line with Vrieling et al's study (2011), we did not find clear differences in RT or HT use versus low levels of 25-OHD. Various studies have also shown that obesity and lower physical activity are associated with low serum levels of vitamin D in patients with BC (Lagunova et al, 2010;Vrieling et al, 2011;Friedman et al, 2012). In our study, according to the univariate analysis BMI>25 was found significantly associated with low levels of vitamin D levels, however correlation was not significant in multivariate analysis.…”
Section: Discussioncontrasting
confidence: 51%
“…First, in a reanalysis of the Women's Health Initiative dietary modification randomized control trial, a nonsignificant increased CRC risk was observed with the vitamin D/calcium supplementation among those who received estrogen therapy, whereas nonsignificant reduced risk was observed among the placebo group of the estrogen trial (67), suggesting that estrogen therapy could interact with vitamin D/calcium on CRC risk. Second, Lagunova and colleagues suggested that the direct relationship between obesity and CRC risk could be partly mediated by a decrease of 25-hydroxyvitamin D level with increasing body mass index (68). Next, it has been suggested that vitamin D and calcium may interact and both may be required to decrease the cancer risk (69).…”
Section: Discussionmentioning
confidence: 99%